The Effectiveness of The Teenagers' Friends Website Educational Media to Improve Teenagers' Knowledge About Free Sex at State Vocational School 8 Pekanbaru - Dewinny Septalia Dale; Intan Maharani; Hamidah Sari Batubara; Andriani (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2026)
Premarital sex refers to sexual behavior between two individuals who are not legally married and is frequently found among adolescents due to a lack of knowledge and comprehensive sexual education. A preliminary survey at SMK Negeri 8 Pekanbaru revealed cases of pregnancy outside marriage. Objective: This study aimed to evaluate the effectiveness of a website-based educational medium in improving adolescents’ knowledge about premarital sex at SMK Negeri 8 Pekanbaru. Methods: This study employed a pre- experimental design with a one-group pre-test and post-test approach. A total of 67 tenth- grade students were selected through total sampling. Data were collected using aquestionnaire administered before and after the educational intervention delivered through the "Teman Remaja" website. Results: Findings showed that prior to the intervention, most respondents had fair to poor knowledge levels (24 students; 35.8%). After the intervention, knowledge levels improved, with 47 students (70.1%) reaching a good level. A paired samplet-test revealed a p-value <0.001, indicating a significant difference in knowledge levels before and after the intervention. Conclusion: The "Teman Remaja" website-based education effectively improved adolescents’ knowledge about premarital sex and can serve as an alternative strategy for promoting adolescent reproductive health, with potential for further development through extended and sustainable implementation. (250 Word), (Georgia 11 with 1,15 space).